Interstitial cells of Cajal and human colon motility in health and disease - Huizinga, Jan D.; Hussain, Amer; Chen, Ji-Hong (American journal of physiology: Gastrointestinal and liver physiology, 2021)
Our understanding of human colonic motility, and autonomic reflexes that generate motor patterns, has increased markedly through high-resolution manometry. Details of the motor patterns are emerging related to frequency and propagation characteristics that allow linkage to interstitial cells of Cajal (ICC) networks. In studies on colonic motor dysfunction requiring surgery, ICC are almost always abnormal or significantly reduced. However, there are still gaps in our knowledge about the role of ICC in the control of colonic motility and there is little understanding of a mechanistic link between ICC abnormalities and colonic motor dysfunction. This review will outline the various ICC networks in the human colon and their proven and likely associations with the enteric and extrinsic autonomic nervous systems. Based on our extensive knowledge of the role of ICC in the control of gastrointestinal motility of animal models and the human stomach and small intestine, we propose how ICC networks are underlying the motor patterns of the human colon. The role of ICC will be reviewed in the autonomic neural reflexes that evoke essential motor patterns for transit and defecation. Mechanisms underlying ICC injury, maintenance, and repair will be discussed. Hypotheses are formulated as to how ICC dysfunction can lead to motor abnormalities in slow transit constipation, chronic idiopathic pseudo-obstruction, Hirschsprung’s disease, fecal incontinence, diverticular disease, and inflammatory conditions. Recent studies on ICC repair after injury hold promise for future therapies.